Formy wsparcia pacjenta i rodziny w sytuacji choroby o zróżnicowanym przebiegu - Kołecka, Barbara; Kołecka, Aleksandra (Studia Edukacyjne, 2022)
The essence of the crisis situation is the breakdown of the current hierarchy of values, the reorganization of everyday life, the intensification of cognitive and emotional efforts to ensure relative intrapsychic homeostasis, and the psychosocial balance in various areas of life (including family and professional life). One of the crisis events is a disease that changes the daily life of individuals and their relatives. The aim of this study is to provide psychological characteristics of the patient in the situation of the disease with its various course, to present the consequences of the appearance of the disease on the level of intrapsychic and social life, and to indicate possible forms of intervention and support for people experiencing their own disease or the disease of a person in the family. An issue worth emphasizing is the provision of specialized, multi-level support for patients and families in the ongoing disease process. Appropriate and responsible therapeutic interactions in the cognitive and emotional dimensions can effectively reduce anxiety and stress reactions and thus contribute to better coping in a crisis situation.